Adolescence Awareness: A Better Tool to Combat HIV/AIDS - Anurag Srivastava; Syed Esam Mahmood; Payal Mishra; V P Shrotriya; Iram Shaifali (Medsci Publications, 2011)
Adolescents are exposed to the risk of being victims of HIV/AIDS, mostly because of a low level of awareness of HIV/AIDS and inadequate access to HIV prevention and treatment services. School education has been described as a 'social vaccine', and it can serve as a powerful preventive tool. The objective is to assess awareness of HIV/AIDS amongst adolescents of District Bareilly. The cross-sectional study involved 341 students, aged 11-19 years. A study instrument was used to assess study subjects' level of awareness regarding modes of transmission, preventive and curative measures of HIV/AIDS and the attitude towards PLWHA. Chi- square test was used to analyze data. The awareness regarding modes of transmission, methods of prevention and treatment was found to be significantly higher among boys as compared to girls (P <.001).  There is a low level of awareness of HIV/AIDS amongst adolescents of District Bareilly. The challenge lies in developing programmes to spread awareness and to induce behavioral changes among them.